2016
DOI: 10.1186/s12886-016-0274-5
|View full text |Cite
|
Sign up to set email alerts
|

Vision-targeted health related quality of life in older adults: patient-reported visibility problems in low luminance activities are more likely to decline than daytime activities

Abstract: BackgroundCommonly used vision-targeted health-related quality of life questionnaires almost exclusively focus items on vision under daytime conditions. Older adults even when in good eye health frequently report experiencing vision problems at night and under low environmental light levels, and psychophysical studies also document these visibility problems. Here we compare the progression of self-reported low luminance visibility problems and self-reported visibility problems under daytime conditions in older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…Further, when analysis is limited to the three studies with the full set of NEI-VFQ-25 subscale scores (i.e., SCORE2, CRUISE and BRAVO), the mean subscale scores are highly correlated with each other, with rank correlation coefficients ranging from 0.97 to 0.99. Similarly, the mean subscale scores of the normal vision populations studied by Mangione, 10 Owsley, 15 and Chia 16 are highly correlated, with coefficients ranging from 0.86 to 0.97. In contrast, correlations between the three retinal vein occlusion and three normal vision reference groups are weaker, ranging from 0.67 to 0.80.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Further, when analysis is limited to the three studies with the full set of NEI-VFQ-25 subscale scores (i.e., SCORE2, CRUISE and BRAVO), the mean subscale scores are highly correlated with each other, with rank correlation coefficients ranging from 0.97 to 0.99. Similarly, the mean subscale scores of the normal vision populations studied by Mangione, 10 Owsley, 15 and Chia 16 are highly correlated, with coefficients ranging from 0.86 to 0.97. In contrast, correlations between the three retinal vein occlusion and three normal vision reference groups are weaker, ranging from 0.67 to 0.80.…”
Section: Resultsmentioning
confidence: 92%
“…10,15,16 Each of the 3 normal vision reference populations was an elderly population, similar to SCORE2, and all had approximately 20/20 vision (Table 1). The NEI-VFQ-25 scores of the 3 normal vision reference populations were similar to each other, and all mean NEI-VFQ-25 subscale scores in these populations were higher than those observed in SCORE2 participants (Table 5A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, there has been a notable emphasis in the recent literature on the importance of such measures across the fields of medicine, particularly in ophthalmology. 4 , 14 18 Currently, the National Eye Institute's Visual Function Questionnaire-25 (NEI VFQ-25) is the most widely used PRO for measuring vision-related quality of life. 16 However, a majority of its questions refer to daytime activities.…”
mentioning
confidence: 99%
“…They had more difficulties with moving around in dim lighting, loss of peripheral vision, and declining driving ability and confidence. Owsley et al 26 also found that adults 60 years of age and older even with normal macular health generally reported notable declines in their vision-related quality of life after 3 years, especially with seeing at night and under low luminance condition.…”
Section: Discussionmentioning
confidence: 95%